Vegetable Proteins as Encapsulating Agents: Recent Updates and Future Perspectives - Islam, F; Amer Ali, Y; Imran, A; Afzaal, M; Zahra, SM; Fatima, M; Saeed, F; Usman, I; Shehzadi, U; Mehta, S; Shah, MA (Wiley, 2023)
The use of proteinaceous material is desired as it forms a protective gelation around the active core, making it safe through temperature, pH, and O2 in the stomach and intestinal environment. During the boom of functional food utilization in this era of advancement in drug delivery systems, there is a dire need to find more protein sources that could be explored for the potential of being used as encapsulation materials, especially vegetable proteins. This review covers certain examples which need to be explored to form an encapsulation coating material, including soybeans (conglycinin and glycinin), peas (vicilin and convicilin), sunflower (helianthins and albumins), legumes (glutenins and albumins), and proteins from oats, rice, and wheat. This review covers recent interventions exploring the mentioned vegetable protein encapsulation and imminent projections in the shifting paradigm from conventional process to environmentally friendly green process technologies and the sensitivity of methods used for encapsulation. Vegetable proteins are easily biodegradable and so are the procedures of spray drying and coacervation, which have been discussed to prepare the desired encapsulated functional food. Coacervation processes are yet more promising in the case of particle size formation ranging from nano to several hundred microns. The present review emphasizes the significance of using vegetable proteins as capsule material, as well as the specificity of encapsulation methods in relation to vegetable protein sensitivity and the purpose of encapsulation accompanying recent interventions.
Keywords: active; coacervation; core; encapsulation; spray drying; vegetable proteins; 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; 0908 Food Sciences; 1111 Nutrition and Dietetics; 3006 Food sciences; 3210 Nutrition and dietetics